Early plasma monocyte chemoattractant protein 1 predicts the development of sepsis in trauma patients: A prospective observational study. Issue 14 (April 2018) - Wang, Yuchang; Liu, Qinxin; Liu, Tao; Zheng, Qiang; Xu, Xi'e; Liu, Xinghua; Gao, Wei; Li, Zhanfei; Bai, Xiangjun
Abstract : Abstract: Monocyte chemoattractant protein 1 (MCP-1) is an initiating cytokine of the inflammatory cascade. Extracellular MCP-1 exhibits pro-inflammatory characteristic and plays a central pathogenic role in critical illness. The purpose of the study was to identify the association between plasma MCP-1 levels and the development of sepsis after severe trauma. The plasma levels of MCP-1 in severe trauma patients were measured by a quantitative enzyme-linked immune sorbent assay and the dynamic release patterns were recorded at three time points during seven days post-trauma. The related factors of prognosis were compared between sepsis and non-sepsis groups and analyzed using multivariate logistic regression analysis. We also used receiver operating characteristic (ROC) curves to assess the values of different variables in predicting sepsis. A total of 72 patients who met criteria indicative of severe trauma (72.22% of male; mean age, 49.40 ± 14.29 years) were enrolled. Plasma MCP-1 concentrations significantly increased on post-trauma day 1 and that this increase was significantly correlated with the Injury Severity Score (ISS) and interleukin-6 (IL-6). Multivariate logistic regression analysis showed that early MCP-1, ISS, and IL-6 were independent risk factors for sepsis in severe trauma patients. Incorporation of the early MCP-1 into the ISS can increase the discriminative performance for predicting development of sepsis. Early plasma MCP-1 concentrations can be used to assess the severity of trauma and is correlated with the development of sepsis after severe trauma. The addition of the early MCP-1 levels to the ISS significantly improves its ability to predict development of sepsis. Abstract : Supplemental Digital Content is available in the text